Sickle Cell Anemia in the Boqueirão Kilombo Community, Bahia, Brazil - Silva, Robson Amaro Augusto da; Group, Studant; Amarim, Maise Mendonça; Figueiredo, Tiana Baqueiro; Gestinari, Raquel de Souza; Tomazi, Laize (Scientia Plena, 2016)
Sickle cell anemia (SCA) is the most common monogenic hereditary disease in Brazil. The North and Northeastern regions of Brazil concentrate a large number of outstanding African ancestry communities, denominated kilombo. The aim of this study was to make a survey of SCA cases in the Boqueirão Kilombo community, situated in Bahia semi-arid region. Individuals from the 467 who replied positively for the occurrence of jaundice, and family history of sickle cell anemia were pre-selected to undergo the diagnostic exam for sickle cell anemia and included in the Group 1. The others individuals were included in the Group 2. Blood samples evaluation of Group 1 showed the following hemoglobin genotypes: HbAA in 65 individuals, HbSS in 3 individuals and HbAS in 29 individuals, HbAF in 1 individual and HbAC in 2 individuals. One of the individuals with SCA and all the heterozygots for the mutated allele S did not know that they had the mutation. The survey data demonstrate the need for health assistance directed towards these special communities.